Kurikulum Fikih dalam Bingkai Negara Kesatuan Republik Indonesia: Upaya Membangun Peradaban Islam berbasis NKRI (UINSI Samarinda, 2016)
Despite having a population that is predominantly Muslim, Indonesia is not an Islamic state; instead, it is a unitary state with different ethnic, tribal, cultural and religious views. Therefore, the awareness of Indonesian people toward the concept of plurality is instrumental in social life. This article attempts to discuss the need for a method in learning Islamic law that leads to the cognizance of the importance of plurality. By using content analysis method, this study focuses on finding learning methods of Islamic law within the framework of the Negara Kesatuan Republik Indonesia (NKRI, Unitary Republic of Indonesia). It finds that all textbooks on Islamic law taught at secondary schools have deficiencies in addressing Indonesian diversity in an inclusive manner. Hence, more reading materials that touches on issues of plurality in the interest of the state and nation are badly needed. The results of this study confirm that the plurality-sensitive Islamic jurisprudence (fiqh) can be implemented in two ways: first, through education; and second through reforming the body of fiqh itself. When the concept of fiqh is unresponsive toward the phenomenon of pluralism and human rights, then its manifestations by Muslims may also envisage this very own fiqh concept. Keywords: contextuality of fiqh, Unitary Republic of Indonesia, plurality education in Indonesia